Composite lithium supplement particle, lithium supplement slurry and preparation method and application thereof

By using the wrinkled structure inert layer formed by microbial pyrolysis products in lithium-ion batteries on the composite lithium-supplement particles, the problems of low first charging efficiency of lithium-ion batteries and poor stability of positive electrode lithium-ion agent are solved, and the high level of lithium-ion batteries is achieved First effect and long cycle life.

CN119297280APending Publication Date: 2025-01-10JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411296027.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the first charging process of lithium-ion batteries, the formation of SEI film causes excessive lithium ions to be consumed, which affects the battery capacity and energy density. It is especially serious in the silicon-based negative electrode and high-nickel ternary system. There is currently a positive electrode lithium supplement agent. Due to problems such as poor stability and large impedance, it is difficult to achieve long-term lithium supplementation.

Method used

Using microbial pyrolytic products to form an inert layer with wrinkle structure on the surface of composite lithium supplement particles, improve the conduction capacity of lithium ions and electrons, and achieve long-term lithium supplementation. By using composite lithium supplementation particles and corresponding lithium supplementation in lithium-ion batteries The slurry is subjected to positive electrode lithium supplementation.

Benefits of technology

Effectively reduce the internal resistance of the battery, achieve slow release of lithium ions, improve the cycle life and rate performance of the battery, and combine high first-term efficiency and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297280A_ABST
    Figure CN119297280A_ABST
Patent Text Reader

Abstract

The invention discloses a composite lithium supplement particle, a lithium supplement slurry and a preparation method and application thereof, the composite lithium supplement particle comprises a lithium supplement particle and an inert layer which coats the surface of the lithium supplement particle and has a wrinkle structure, and the inert layer comprises a microbial pyrolysis product. The invention also provides lithium supplementing slurry, and a preparation method of the lithium supplementing slurry comprises the following steps: (1) heating and stirring the lithium supplementing particles and microorganisms in the presence of a solvent to obtain a mixture; and (2) adding a conductive agent and a binder into the mixture, and stirring to obtain the lithium supplementing slurry containing the composite lithium supplementing particles. When the composite lithium supplement particles or the lithium supplement slurry is used for lithium supplement of the positive electrode of the battery, contact sites of ions can be effectively increased, an ion transmission path can be shortened, the electron conductivity can be enhanced, meanwhile, the lithium supplement particles can slowly release lithium ions in the charge-discharge cycle process of the battery, long-acting lithium supplement is achieved, and the service life of the battery is prolonged. Therefore, the battery containing the lithium supplement particles has high first efficiency, high rate capability and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite lithium supplement particle, a lithium supplement slurry, and a preparation method and application thereof. Background Art

[0002] During the first charge of a lithium-ion battery, the organic electrolyte will be reduced and decomposed on the surface of the negative electrode such as graphite to form a solid electrolyte interface (SEI) film, which permanently consumes a large amount of lithium from the positive electrode, resulting in a low coulombic efficiency (ICE) of the first cycle, reducing the capacity and energy density of the lithium battery. This problem is more serious in a high-energy-density system with a silicon-based negative electrode and a high-nickel ternary. This is because the silicon-based negative electrode material undergoes severe volume expansion during the battery's cyclic charge and discharge process, which causes the SEI film to rupture continuously, and the subsequent continuous repair process will continue to consume lithium in the positive electrode, which seriously affects the battery capacity.

[0003] Therefore, the "pre-lithiation technology" was proposed, which replenishes lithium ions by adding lithium to the inside of the lithium-ion battery before the battery works. At present, the main route of pre-lithiation is positive electrode lithium replenishment, which is achieved by adding lithium replenishers (such as binary lithium compounds, lithium-rich positive electrode materials, lithium complexes, etc.). However, these positive electrode lithium replenishers have their own disadvantages when replenishing lithium to the battery. For example, the binary lithium compound Li2O as a lithium replenisher has a high specific capacity, but poor conductivity, which affects the rate performance of the battery; the lithium-rich compound LNO (Li2NiO2) / LFO ((Li5FeO4) has poor stability and high impedance; the lithium complex Li2S / Co has a high specific capacity, good conductivity and stability, and its complex structure can fix the intermediate product polysulfide to prevent it from irreversibly reacting with the carbonate electrolyte, but after delithiation, there is a trace amount of inactive CoS2 residue, which continues to accumulate in a long cycle and increases the internal resistance of the battery. In addition, although the current direct addition of lithium replenishers to the positive electrode can solve the problem of low initial coulomb efficiency of the battery, it is difficult to achieve long-term lithium replenishment. Summary of the invention

[0004] To solve the above problems, the present invention provides a composite lithium-replenishing particle, a lithium-replenishing slurry, and a preparation method and application thereof. Thermal decomposition of microorganisms is used to form an inert layer of carbon-containing impurities with a wrinkled structure on the surface of the lithium-replenishing particle. The formation of the inert layer can not only promote the conduction of lithium ions and electrons and reduce the internal resistance of the battery, but also help the lithium-replenishing particles to slowly release lithium ions during the charge and discharge cycle, thereby achieving long-term lithium replenishment.

[0005] Specifically, the following technical solutions are provided:

[0006] A first aspect of the present invention provides a composite lithium supplement particle, which comprises a lithium supplement particle and an inert layer having a wrinkled structure coated on the surface of the lithium supplement particle, wherein the inert layer comprises a microbial pyrolysis product.

[0007] Furthermore, the lithium-supplementing particles include one or more of binary lithium compounds, lithium-rich compounds, and lithium complexes; the binary lithium compounds include but are not limited to Li2O and LiF, the lithium-rich compounds include but are not limited to Li2NiO2 and LiFeO4, and the lithium complexes include but are not limited to Li2S / Co complexes.

[0008] Furthermore, the microorganism is a fungus and / or a bacterium; the fungus includes yeast, and the bacteria includes actinomycetes.

[0009] Furthermore, the particle size of the lithium supplement particles is preferably 100-500 nm.

[0010] Furthermore, the thickness of the inert layer is preferably 95-220 nm.

[0011] Furthermore, the particle size of the composite lithium supplement particles is 500nm-5μm.

[0012] Furthermore, the microbial pyrolysis product is a pyrolysis product of microorganisms at 60-80° C., and the pyrolysis product contains carbon impurities.

[0013] The second aspect of the present invention provides a method for preparing the composite lithium supplement particles described in the first aspect, wherein the lithium supplement particles and microorganisms are subjected to heating and stirring treatment in the presence of a solvent under an inert atmosphere to obtain the composite lithium supplement particles, wherein the heating and stirring treatment temperature is 60-80°C, and the heating and stirring treatment time is not less than 30 minutes.

[0014] Furthermore, the inert atmosphere is formed by one or more gases selected from the group consisting of nitrogen, helium, neon and argon.

[0015] Furthermore, the solvent is N-methylpyrrolidone (NMP).

[0016] Furthermore, the heating and stirring treatment is preferably carried out in an oil bath.

[0017] Furthermore, the heating and stirring treatment time is preferably 2-12 h, for example 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc.

[0018] Furthermore, the lithium supplement particles and the microorganisms are first subjected to dry stirring treatment, and after being evenly mixed, a solvent is added for wet stirring treatment to obtain the composite lithium supplement particles; the temperature of the dry stirring treatment and the wet stirring treatment is preferably 60-80°C, and the time of the wet stirring treatment is not less than 0.5h.

[0019] The third aspect of the present invention further provides a lithium supplement slurry, comprising the composite lithium supplement particles described in the first aspect or the composite lithium supplement particles prepared by the preparation method described in the second aspect.

[0020] Furthermore, the formula of the lithium supplement slurry comprises the following components by mass: 50-60 parts of lithium supplement particles, 10-25 parts of microorganisms, 10-25 parts of conductive agent, and 5-20 parts of binder.

[0021] Furthermore, when the lithium-replenishing particles are binary lithium compounds, the formula of the lithium-replenishing slurry preferably comprises the following components by mass: 50-60 parts of lithium-replenishing particles, 10-20 parts of microorganisms, 15-25 parts of conductive agent, and 5-15 parts of binder.

[0022] Furthermore, when the lithium-replenishing particles are lithium-rich compounds, the formula of the lithium-replenishing slurry preferably comprises the following components by mass: 50-60 parts of lithium-replenishing particles, 10-20 parts of microorganisms, 10-20 parts of conductive agents, and 10-20 parts of binders.

[0023] Furthermore, when the lithium-replenishing particles are lithium composites, the formula of the lithium-replenishing slurry preferably comprises the following components by mass: 50-60 parts of lithium-replenishing particles, 20-25 parts of microorganisms, 10-20 parts of conductive agents, and 5-15 parts of binders.

[0024] Furthermore, the conductive agent can be selected from one or more of conductive carbon black, conductive graphite, conductive fiber, carbon nanotubes, and graphene; the binder can be selected from one or more of PVDF (polyvinylidene fluoride), SBR (styrene-butadiene rubber), CMC (sodium carboxymethyl cellulose), PAA (polyacrylic acid), PAN (polyacrylonitrile), SA (sodium alginate), PVA (polyvinyl alcohol), PMMA (polymethyl methacrylate), HNBR (hydrogenated nitrile rubber), and PTFE (polytetrafluoroethylene).

[0025] The fourth aspect of the present invention provides a method for preparing the lithium supplement slurry according to the third aspect, comprising the following steps:

[0026] (1) Under an inert atmosphere, stirring the lithium supplement particles and the microorganisms in the presence of a solvent at 60-80° C. for not less than 30 minutes to obtain a mixture;

[0027] (2) Adding a conductive agent and a binder to the mixture prepared in step (1) and stirring the mixture to obtain a lithium supplement slurry containing composite lithium supplement particles.

[0028] Furthermore, in step (1), the stirring time is preferably 1-3 h.

[0029] Furthermore, in step (1), the lithium supplement particles and the microorganisms are first subjected to dry stirring treatment, and after being evenly mixed, a solvent is added for wet stirring treatment to obtain a mixture; preferably, the dry stirring treatment time is 0.5-1.5h, and the wet stirring treatment time is not less than 0.5h, for example 1h; the temperature of the dry stirring treatment and the wet stirring treatment is 60-80°C.

[0030] Furthermore, in step (2), the temperature of the stirring treatment is preferably 60-80° C., and the time is preferably 3-11 h, such as 4-10 h.

[0031] A fifth aspect of the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer is obtained by coating a positive electrode slurry on the current collector and drying it;

[0032] The positive electrode slurry comprises the composite lithium supplement particles described in the first aspect or the lithium supplement slurry described in the third aspect; and / or,

[0033] The positive electrode plate also includes a lithium replenishing layer, which is arranged on a side of the positive electrode active layer away from the current collector or on a side of the current collector where the positive electrode active layer is not arranged; the lithium replenishing layer is obtained by coating the lithium replenishing slurry described in the third aspect on the current collector or the positive electrode active layer and drying it.

[0034] Furthermore, the single-surface density of the positive electrode active layer is preferably 50-300 mg / 1540.25 mm2.

[0035] Furthermore, when the positive electrode slurry contains the lithium replenishing slurry, 2%≤(yb) / (xa)≤8% is satisfied, wherein x is the content of the positive electrode slurry, a is the solid content of the positive electrode slurry, y is the content of the lithium replenishing slurry added to the positive electrode slurry, and b is the solid content of the lithium replenishing slurry.

[0036] Furthermore, the thickness of the lithium replenishing layer is preferably 0.5-20 μm.

[0037] The sixth aspect of the present invention provides a lithium battery comprising the positive electrode sheet described in the fifth aspect.

[0038] Furthermore, the lithium battery also includes a negative electrode plate, the negative electrode plate includes a silicon-based negative electrode material, and the silicon-based negative electrode material includes one or more of nano-silicon, silicon monoxide, silicon nanowires or gas-phase silicon carbon.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention uses microbial inactivation and pyrolysis to form a carbon-containing impurity inert layer with a wrinkled structure on the surface of lithium supplement particles to obtain a composite lithium supplement particle. The inert layer with a wrinkled structure can increase the lithium ion contact sites on the surface of the lithium supplement particle and shorten the lithium ion transmission path. At the same time, the inert layer contains carbon-containing impurities, which is conducive to improving the electronic conductivity of the lithium supplement particles, thereby effectively reducing the internal resistance of the battery; in addition, the presence of the inert layer enables the lithium supplement particles to slowly release lithium ions during the charge and discharge cycle, thereby achieving long-term lithium supplementation and improving the cycle life of the battery.

[0041] In addition, the present invention also provides a series of lithium replenishing slurries. According to the performance differences of lithium replenishing particles, by adjusting the contents of lithium replenishing particles, microorganisms, conductive agents and binders in the lithium replenishing slurry formula, the prepared lithium replenishing slurry containing composite lithium replenishing particles can effectively improve the defects of each lithium replenishing particle when used for positive electrode lithium replenishment.

[0042] The lithium battery constructed by the present invention using the above-mentioned composite lithium replenishment particles for positive electrode lithium replenishment can not only achieve the first lithium replenishment and long-term lithium replenishment, but also promote ion and electron conduction to a certain extent, so that the lithium battery can have high first efficiency, long cycle life and excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The SEM images of lithium-supplementing particles before and after Li2NiO2 coating; a is the lithium-supplementing particles before coating, and b is the composite lithium-supplementing particles after coating;

[0044] Figure 2 TEM images of lithium-replenishing particles before and after Li2NiO2 coating; A is the lithium-replenishing particle before coating, and B is the composite lithium-replenishing particle after coating. DETAILED DESCRIPTION

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."

[0046] As described in the background technology, since the formation of the negative electrode SEI film of the lithium-ion battery during the first charging process will consume a large amount of lithium from the positive electrode, and the repair of the SEI film during the cyclic charge and discharge process will continue to consume the lithium in the positive electrode, it will seriously affect the capacity and cycle life of the battery. At present, there is a method of adding a lithium replenisher to the positive electrode active layer or setting a lithium replenisher layer containing a lithium replenisher at the positive electrode to achieve positive electrode lithium replenishment, but the existing positive electrode lithium replenishers generally have problems such as poor stability and high impedance. Therefore, directly adding the above-mentioned lithium replenisher for positive electrode lithium replenishment often increases the internal resistance of the battery, affects the battery rate performance, and is difficult to achieve long-term lithium replenishment.

[0047] To solve the above problems, the embodiments of the present invention provide a composite lithium-supplementing particle, which comprises a lithium-supplementing particle and an inert layer having a wrinkled structure coated on the surface of the lithium-supplementing particle, wherein the inert layer comprises a microbial pyrolysis product; in some preferred embodiments of the present invention, the inert layer is obtained by inactivating and pyrolyzing the microorganisms adsorbed on the surface of the lithium-supplementing particle at 60-80°C.

[0048] In order to solve the problems of large impedance, poor stability, and inability to achieve long-term lithium replenishment in the lithium replenishment particles currently used for positive electrode lithium replenishment, the present invention provides a composite lithium replenishment particle, which utilizes microbial inactivation and pyrolysis to form an inert layer on the surface of the lithium replenishment particle, which can effectively improve the problems of large impedance and poor stability of the lithium replenishment particles, and can achieve long-term lithium replenishment. Specifically, the inert layer formed by the inactivation and pyrolysis of microorganisms on the surface of lithium-replenishing particles has a wrinkled structure, which can increase the lithium ion contact sites on the surface of lithium-replenishing particles, provide more lithium ion transmission channels, and make the gaps between particles in the positive electrode active layer or lithium-replenishing layer containing the composite lithium-replenishing particles smaller, which helps to shorten the lithium ion transmission path, accelerate the transmission of lithium ions to the negative electrode, and avoid the formation of the negative electrode SEI film to consume more lithium in the positive electrode active material; in addition, since the cell wall of the microorganism is mainly composed of polysaccharides and protein substances, it can be thermally decomposed to obtain carbon-containing impurities. Such carbon-containing impurities are beneficial to improving electronic conductivity, and the synergistic effect of the wrinkled structure on ion conduction. Using the above-mentioned composite lithium-replenishing particles for positive electrode lithium replenishment can effectively reduce the internal resistance of the battery. Even in the process of cyclic charge and discharge, the trace inactive carbon-containing impurities remaining after the composite lithium-replenishing particles are delithiated can still play a conductive role, which is beneficial to reducing the internal resistance of the battery. In addition, the coating of the inert layer can effectively improve the stability of the lithium-supplementing particles, and enable the lithium-supplementing particles to slowly release lithium ions during the charge and discharge cycle, thereby achieving a long-term lithium replenishment effect and improving the cycle life of the battery.

[0049] In the present invention, the above-mentioned lithium-supplementing particles can be selected from one or more of binary lithium compounds, lithium-rich compounds, and lithium complexes, such as Li2O, LiF-type binary lithium compounds, Li2NiO2, LiFeO4-type lithium-rich compounds, Li2S / Co lithium complexes, etc. The types of lithium-supplementing particles that can be used in the present invention include but are not limited to the lithium-containing compounds listed above.

[0050] In the present invention, the microorganisms are fungi and / or bacteria, including yeast, actinomycetes, etc. The microorganisms adsorbed on the surface of the lithium-supplementing particles can be inactivated by temperature-controlled heating to form a wrinkled structure. The cell walls of such microorganisms are mainly composed of peptidoglycan polysaccharides and proteins, which can be decomposed to form carbon-containing impurities during the heat treatment process. It is found that such carbon-containing impurities help to enhance the electronic conductivity of the lithium-supplementing particles.

[0051] In the present invention, the composite lithium-supplementing particles have a core-shell structure, including lithium-supplementing particles located in the core layer and an inert layer located in the shell layer, wherein the particle size of the lithium-supplementing particles is preferably 100-500nm; the thickness of the inert layer is preferably 95-220nm, and during the growth process, the thickness of the inert layer shows a trend of first increasing and then stabilizing. In order to obtain an inert layer with perfect growth and obvious wrinkle structure to play an effective isolation role and improve the effect of ion and electron conduction, preferably, the thickness of the inert layer is controlled in the range of 95-220nm, such as 100±5nm, 180±10nm, 200±20nm, etc., or any value within the above range; the particle size of the composite lithium-supplementing particles formed by agglomerating lithium-supplementing particles coated with the inert layer is 500nm-5μm.

[0052] The present invention also provides a method for preparing the composite lithium supplement particles, which is as follows:

[0053] Under an inert atmosphere, the lithium supplement particles and microorganisms are heated and stirred in the presence of a solvent to obtain the composite lithium supplement particles. The temperature of the heating and stirring treatment is 60-80° C., and the heating and stirring treatment time is not less than 30 minutes.

[0054] In the present invention, the temperature of the heating and stirring treatment needs to be controlled within the range of 60-80°C to obtain an inert layer with a distinct wrinkle structure and a high content of carbon impurities. If the temperature is too low, the wrinkle formation and growth are incomplete. If the temperature is too high, the microbial cell wall decomposes too quickly, and less carbon impurities remain in the inert layer.

[0055] In some preferred embodiments of the present invention, the inert atmosphere is formed by one or more gases selected from nitrogen, helium, neon and argon; the solvent may be selected from N-methylpyrrolidone (NMP), or other solvents that do not react with the lithium supplement particles.

[0056] In the present invention, the heating and stirring treatment is preferably carried out in an oil bath, such as a silicone oil bath. The heating and stirring treatment is carried out using oil bath stirring technology. On the one hand, the temperature can be better controlled to make the temperature consistency during the stirring treatment better. On the other hand, the lithium supplement particles have poor stability and cannot come into contact with aqueous solutions, air, etc. The use of oil bath stirring technology combined with the introduction of inert gas is conducive to isolating the air, ensuring the effectiveness of the lithium supplement particles and the safety of the reaction.

[0057] In the present invention, if the heating and stirring time is too short, the inert layer formed on the surface of the lithium-supplemented particles is imperfect, and as the heating and stirring time increases, the thickness of the inert layer first increases and then stabilizes during the growth process. In order to obtain a complete inert layer while reducing energy consumption, preferably, the time of the above-mentioned heating and stirring treatment is controlled in the range of 2-12h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.; wherein, the thickness of the inert layer is 100±5nm when heated and stirred for 6-8h; the thickness of the inert layer is 180±10nm when heated and stirred for 8-10h; the thickness of the inert layer is 200±20nm when heated and stirred for 10-12h; and the thickness of the inert layer is 200±20nm when heated and stirred for more than 12h.

[0058] In some preferred embodiments of the present invention, the lithium-replenishing particles and microorganisms are first subjected to dry stirring at 60-80°C, and after being evenly mixed, a solvent is added and wet stirring is carried out at 60-80°C to obtain composite lithium-replenishing particles; preferably, the dry stirring time is 0.5-1.5h, and the wet stirring time is not less than 0.5h.

[0059] In addition, the embodiments of the present invention provide a lithium supplement slurry comprising the above-mentioned composite lithium supplement particles.

[0060] In the present invention, the formula of the lithium supplement slurry comprises the following components by mass: 50-60 parts of lithium supplement particles, 10-25 parts of microorganisms, 10-25 parts of conductive agents, and 5-20 parts of binders; wherein, when the lithium supplement particles are binary lithium compounds, the formula of the lithium supplement slurry preferably comprises the following components by mass: 50-60 parts of lithium supplement particles, 10-20 parts of microorganisms, 15-25 parts of conductive agents, and 5-15 parts of binders. The conductivity of binary lithium compounds is poor. By increasing the content of the conductive agent, the effect of positive electrode lithium supplement on battery impedance can be improved; when the lithium supplement particles are lithium-rich compounds, the formula of the lithium supplement slurry preferably comprises the following components by mass: 50-60 parts of lithium supplement particles, 10-20 parts of microorganisms, 10-20 parts of conductive agents, and 10-20 parts of binders. The stability of lithium-rich compounds is poor, and the content of the lithium supplement slurry is appropriately increased. The content of the binder in the material is increased, and the stability of the lithium supplement particles is further improved by coating the particles with the binder; when the lithium supplement particles are lithium complexes, the formula of the lithium supplement slurry preferably comprises the following components by mass: 50-60 parts of lithium supplement particles, 20-25 parts of microorganisms, 10-20 parts of conductive agents, and 5-15 parts of binders. Lithium complexes such as Li2S / Co have trace amounts of inactive CoS2 residues after delithiation, which continue to accumulate in long cycles and increase the internal resistance of the battery. When preparing lithium supplement slurries using such lithium complexes as lithium supplement particles, the content of microorganisms is appropriately increased, and a large number of wrinkled structures are formed on the surface of the lithium supplement particles by thermal decomposition, thereby shortening the lithium ion transmission path after the slurry is mixed. In addition, the inert layer containing carbonaceous impurities formed by the decomposition of microorganisms still has a trace amount of inactive residual carbon layer after the lithium supplement particles are delithiated during the cycle, which still plays a conductive role and reduces the internal resistance.

[0061] In the above-mentioned lithium supplement slurry, the conductive agent can be selected from one or more of conductive carbon black, conductive graphite, conductive fiber, carbon nanotubes, and graphene; the binder can be selected from one or more of PVDF (polyvinylidene fluoride), SBR (styrene-butadiene rubber), CMC (sodium carboxymethyl cellulose), PAA (polyacrylic acid), PAN (polyacrylonitrile), SA (sodium alginate), PVA (polyvinyl alcohol), PMMA (polymethyl methacrylate), HNBR (hydrogenated nitrile rubber), and PTFE (polytetrafluoroethylene).

[0062] The present invention also provides a method for preparing the lithium supplement slurry, comprising the following steps:

[0063] (1) Under an inert atmosphere, stirring the lithium supplement particles and the microorganisms in the presence of a solvent at 60-80° C. for not less than 30 minutes to obtain a mixture;

[0064] (2) Adding a conductive agent and a binder to the mixture prepared in step (1) and stirring the mixture to obtain a lithium supplement slurry containing composite lithium supplement particles.

[0065] In the present invention, in step (1), the stirring time is preferably 1-3 hours, so that the microorganisms are fully and evenly adsorbed on the surface of the lithium supplementing particles; more preferably, the lithium supplementing particles and the microorganisms are first subjected to dry stirring treatment, and the dry stirring treatment time is 0.5-1.5 hours, for example, 1 hour. After the mixture is evenly mixed, a solvent is added for wet stirring treatment, and the wet stirring treatment time is not less than 0.5 hours to obtain a mixture.

[0066] In the present invention, in step (2), the stirring temperature is preferably 60-80°C, and the time is preferably 3-11 hours; more preferably, in step (1) and step (2), the total stirring time at 60-80°C is 6-12 hours.

[0067] The embodiment of the present invention also provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer is obtained by coating a positive electrode slurry on the current collector and drying it; wherein the positive electrode slurry comprises the lithium replenishing slurry prepared by the above preparation method. The positive electrode active layer is prepared by adding the lithium replenishing slurry comprising the composite lithium replenishing particles into the positive electrode slurry to achieve positive electrode lithium replenishment.

[0068] In the present invention, the single-surface density of the positive electrode active layer is preferably 50-300 mg / 1540.25 mm2, for example 122 mg / 1540.25 mm 2 wait.

[0069] In the present invention, when the positive electrode slurry contains the above-mentioned lithium replenishing slurry, 2%≤(yb) / (xa)≤8% is satisfied, wherein x is the content of the positive electrode slurry, a is the solid content of the positive electrode slurry, y is the content of the lithium replenishing slurry added to the positive electrode slurry, and b is the solid content of the lithium replenishing slurry.

[0070] In addition to the above-mentioned method of adding lithium replenishing slurry to the positive electrode active slurry to achieve positive electrode lithium replenishment, positive electrode lithium replenishment can also be achieved by directly adding composite lithium replenishing particles to the positive electrode active slurry, or by setting a lithium replenishing layer on the surface of the current collector or on the surface of the positive electrode active layer away from the current collector. The lithium replenishing layer can be directly obtained by coating the above-mentioned lithium replenishing slurry on the current collector or the positive electrode active layer and drying it. Preferably, the thickness of the lithium replenishing layer is 0.5-20nm.

[0071] The present invention also provides a lithium battery in the embodiment part, comprising a negative electrode plate and the above-mentioned positive electrode plate, wherein the negative electrode plate comprises a silicon-based negative electrode material, such as one or more of nano-silicon, silicon monoxide, silicon nanowires or gas-phase silicon carbon; the lithium battery exhibits high initial efficiency, long cycle life and excellent rate performance.

[0072] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0073] Example 1

[0074] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery, which are specifically as follows:

[0075] Preparation of lithium supplement slurry:

[0076] Build an oil bath workbench, and place the magnetic stirring heating platform vertically, the wide-mouth beaker with silicone oil, and the three-necked round-bottom beaker in sequence. The three-necked round-bottom beaker has a built-in magnetic stirring rotor, and the bottom half of the bottle is placed in silicone oil. The mouth of the bottle has three openings, one side is connected to the inert air pipe, one side is vented, and the middle side stopper is blocked to facilitate subsequent filling. Place an appropriate amount of lithium-supplementing particles (lithium-rich compound Li2NiO2) in a three-necked beaker, turn on the inert gas argon, and turn on the magnetic stirring; then add microorganisms (activated yeast powder); gradually increase the temperature to 80°C, and continue to stir in a dry method for 1 hour. Then add NMP solvent, maintain the temperature and continue stirring for 1 hour until it is fully mixed to obtain mixture A;

[0077] Then, a conductive agent and a binder were added and stirred for 10 hours, and then the temperature was lowered to 25° C. to obtain a lithium supplement slurry.

[0078] In the formula of the above lithium supplement slurry: the mass ratio of lithium supplement particles (lithium-rich compound Li2NiO2), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 56:18:16:10; the prepared mixture A was sampled with a pipette and placed in a 100°C oven for 80 minutes, and then the dried powder was subjected to SEM and TEM tests. The test results are as follows:

[0079] Figure 1 a, 2a are SEM and TEM images of lithium-rich compound Li2NiO2 of lithium-supplemented particles, respectively. Figure 1 b and 2b are the SEM and TEM images of the powder (composite lithium supplement particles) after drying, respectively. It can be seen from the figures that after stirring and heat treatment, the surface of the lithium supplement particles is coated with a coating layer, and the coating layer has a wrinkled structure, so that there is no obvious dividing line between the particles of the coated lithium supplement particles, and the contact is closer.

[0080] Preparation of lithium battery:

[0081] Preparation of positive electrode sheet: positive electrode active material (nickel 532 in ternary NCM), conductive agent SP, conductive agent CNT, binder PVDF and lithium supplement slurry are mixed in a mass ratio of 95.5%: 0.5%: 0.4%: 0.6%: 3.0% to obtain a mixed material, and the mixed material is fully stirred in NMP to obtain the corresponding positive electrode slurry; the revolution speed of the mixer is 25rmp, and the rotation speed is 2500rmp; the solid content of the positive electrode slurry is 67%, the viscosity range is 9500mpa.s, and the fineness is ≤30μm. The positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil (12μm), and after drying and pressing, a positive electrode sheet with a thickness of 146μm is obtained, and the single-sided coating surface density is 355mg / 1540.25mm 2 , roller compaction density 3.45g / cc.

[0082] Preparation of negative electrode sheets: Mix the negative electrode active material (SiO2), conductive agent SP, conductive agent CNT, binder SBR and binder PAA in a mass ratio of 94.3%: 1.44%: 0.06%: 1.40%: 2.80%, add deionized water and stir to form a uniform and stable negative electrode slurry. The revolution speed of the mixer is 25 rpm and the rotation speed is 3000 rpm; the solid content of the negative electrode slurry is 50%, the viscosity range is 7200 mpa.s, and the fineness is ≤ 30 μm. The negative electrode slurry is evenly coated on the surface of the negative electrode collector copper foil (6 μm). After drying and pressing, a negative electrode sheet with a thickness of 108 μm is obtained, and the single-sided coating surface density is 122 mg / 1540.25 mm 2 , roller compaction density 1.55g / cc.

[0083] The N (negative electrode capacity) / P (positive electrode capacity) ratio in this embodiment is 1.11.

[0084] Isolation membrane: 7μm PE base film, with 3μm PVDF adhesive layer coated on both sides of the PE base film, and 3μm ceramic layer coated on one side (the ceramic layer faces the positive electrode to prevent the risk of high voltage breakdown).

[0085] Electrolyte: Ethylene carbonate EC, dimethyl carbonate DMC, and ethyl methyl carbonate EMC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then solute LiPF6 is added to the organic solvent to dissolve and mix evenly to obtain an electrolyte; wherein the concentration of LiPF6 is 1.2 mol / L.

[0086] Battery assembly: Arrange the positive electrode, separator, and negative electrode in sequence and assemble them by winding; inject the electrolyte into the dry battery cell, soak it for 24 hours, and then complete the battery cell production after the formation and aging processes.

[0087] Example 2

[0088] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery. The difference from the embodiment 1 is that the preparation of the lithium supplement slurry is different, and the positive and negative active materials for constructing the lithium battery are different, specifically:

[0089] The details are as follows:

[0090] Preparation of lithium supplement slurry:

[0091] Build an oil bath workbench, and place the magnetic stirring heating platform vertically, the wide-mouth beaker with silicone oil, and the three-necked round-bottom beaker in sequence. The three-necked round-bottom beaker has a built-in magnetic stirring rotor, and the bottom half of the bottle is placed in silicone oil. The bottle mouth has three openings, one side is connected to the inert air pipe, one side is vented, and the middle side stopper is blocked to facilitate subsequent filling. Place an appropriate amount of lithium-supplementing particles (lithium complex Li2S / Co) in a three-necked beaker, turn on the inert gas argon, and turn on the magnetic stirring; then add microorganisms (activated yeast powder); gradually increase the temperature to 80°C, and continue to stir in a dry method for 1 hour. Then add NMP solvent, maintain the temperature and continue stirring for 1 hour until it is fully mixed to obtain mixture A;

[0092] Then, a conductive agent and a binder were added and stirred for 8 hours, and then the temperature was lowered to 25° C. to obtain a lithium supplement slurry.

[0093] In the formula of the above-mentioned lithium replenishing slurry: the mass ratio of lithium replenishing particles (lithium composite Li2S / Co), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 56:22:12:10.

[0094] Positive electrode active material: An equal amount of NCM622 is used to replace nickel 532 in the ternary NCM in Example 1.

[0095] Negative electrode active material: An equal amount of silicon-carbon composite material (silicon-carbon composite material, the mass ratio of silicon material to carbon material is 7:3) is used to replace SiO2 in Example 1.

[0096] The remaining operations are consistent with those in Example 1, and the corresponding lithium battery is prepared.

[0097] Example 3

[0098] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery, and the difference from the embodiment 2 is only that the preparation of the lithium supplement slurry is different (the stirring time is different), specifically:

[0099] Build an oil bath workbench, and place the magnetic stirring heating platform vertically, the wide-mouth beaker with silicone oil, and the three-necked round-bottom beaker in sequence. The three-necked round-bottom beaker has a built-in magnetic stirring rotor, and the bottom half of the bottle is placed in silicone oil. The bottle mouth has three openings, one side is connected to the inert air pipe, one side is vented, and the middle side stopper is blocked to facilitate subsequent filling. Place an appropriate amount of lithium-supplementing particles (lithium complex Li2S / Co) in a three-necked beaker, turn on the inert gas argon, and turn on the magnetic stirring; then add microorganisms (activated yeast powder); gradually increase the temperature to 80°C, and continue to stir in a dry method for 1 hour. Then add NMP solvent, maintain the temperature and continue stirring for 1 hour until it is fully mixed to obtain mixture A;

[0100] Then, a conductive agent and a binder were added and stirred for 4 hours, and then the temperature was lowered to 25° C. to obtain a lithium supplement slurry.

[0101] In the formula of the above-mentioned lithium replenishing slurry: the mass ratio of lithium replenishing particles (lithium composite Li2S / Co), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 56:22:12:10.

[0102] The remaining operations are consistent with those in Example 2 to prepare the corresponding lithium battery.

[0103] Example 4

[0104] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery. The only difference from Embodiment 2 is that the preparation of the lithium supplement slurry is different (different microorganism species), specifically:

[0105] Build an oil bath workbench, and place the magnetic stirring heating platform vertically, the wide-mouth beaker with silicone oil, and the three-necked round-bottom beaker in sequence. The three-necked round-bottom beaker has a built-in magnetic stirring rotor, and the bottom half of the bottle is placed in silicone oil. The mouth of the bottle has three openings, one side is connected to the inert air pipe, one side is vented, and the middle side stopper is blocked to facilitate subsequent filling. Place an appropriate amount of lithium-supplementing particles (lithium complex Li2S / Co) in a three-necked beaker, turn on the inert gas argon, and turn on the magnetic stirring; then add microorganisms (activated yeast powder and freeze-dried powder actinomycetes, where the mass ratio of yeast to actinomycetes is 1:1); gradually increase the temperature to 80°C, and stir continuously for 1 hour in a dry method. Then add NMP solvent, maintain the temperature and continue stirring for 1 hour until it is fully mixed to obtain mixture A;

[0106] Then, a conductive agent and a binder were added and stirred for 8 hours, and then the temperature was lowered to 25° C. to obtain a lithium supplement slurry.

[0107] In the formula of the above-mentioned lithium replenishing slurry: the mass ratio of lithium replenishing particles (lithium complex Li2S / Co), microorganisms (the mass ratio of yeast and actinomycetes is 1:1), conductive agent (graphene), and binder (polyvinyl alcohol) is 56:22:12:10.

[0108] The remaining operations are consistent with those in Example 1, and the corresponding lithium battery is prepared.

[0109] Example 5

[0110] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery. The difference from the embodiment 2 is that the preparation of the lithium supplement slurry is different, and the positive and negative active materials for constructing the lithium battery are different, specifically:

[0111] Preparation of lithium supplement slurry:

[0112] Build an oil bath workbench, and place the magnetic stirring heating platform vertically, the wide-mouth beaker with silicone oil, and the three-necked round-bottom beaker in sequence. The three-necked round-bottom beaker has a built-in magnetic stirring rotor, and the bottom half of the bottle is placed in silicone oil. The mouth of the bottle has three openings, one side is connected to the inert gas pipe, one side is vented, and the middle side stopper is blocked to facilitate subsequent filling. Place an appropriate amount of lithium-supplementing particles (binary lithium compound Li2O) in a three-necked beaker, turn on the inert gas argon, and turn on the magnetic stirring; then add microorganisms (activated yeast powder); gradually increase the temperature to 80°C, and continue to stir in a dry method for 1 hour. Then add NMP solvent, maintain the temperature and continue stirring for 1 hour until it is fully mixed to obtain mixture A;

[0113] Then, a conductive agent and a binder were added and stirred for 10 hours, and then the temperature was lowered to 25° C. to obtain a lithium supplement slurry.

[0114] In the formula of the above-mentioned lithium replenishing slurry: the mass ratio of lithium replenishing particles (binary lithium compound Li2O), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 56:18:16:10.

[0115] Positive electrode active material: An equal amount of ternary NCM high nickel 811 is used to replace the NCM622 in Example 2.

[0116] Negative electrode active material: An equal amount of SiO2 is used to replace the silicon-carbon composite material in Example 2.

[0117] The remaining operations are consistent with those in Example 2 to prepare the corresponding lithium battery.

[0118] Example 6

[0119] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery. The difference from Embodiment 2 is that the temperature for preparing the lithium supplement slurry is different, and the stirring and heating treatment is performed at 60° C. The remaining operations are consistent with those in Embodiment 2, and the corresponding lithium battery is prepared.

[0120] Example 7

[0121] This embodiment relates to the preparation of a lithium supplement slurry and a lithium battery. The difference from Embodiment 4 is that the temperature for preparing the lithium supplement slurry is different, and the stirring and heating treatment is performed at 70° C. The remaining operations are the same as those in Embodiment 4, and the corresponding lithium battery is prepared.

[0122] Example 8

[0123] This embodiment relates to the preparation of a lithium replenishing slurry and a lithium battery. The only difference from Example 2 is that the formula of the lithium replenishing slurry is different. Specifically, the mass ratio of lithium replenishing particles (lithium complex Li2S / Co), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 69%:5%:16%:10%. The remaining operations are consistent with those in Example 2 to prepare the corresponding lithium battery.

[0124] Example 9

[0125] This embodiment relates to the preparation of a lithium replenishing slurry and a lithium battery. The only difference from Example 2 is that the formula of the lithium replenishing slurry is different, specifically: the mass ratio of lithium replenishing particles (lithium complex Li2S / Co), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 39%:35%:16%:10%, and the remaining operations are consistent with Example 2 to prepare the corresponding lithium battery.

[0126] Example 10

[0127] This embodiment relates to the preparation of a lithium replenishing slurry and a lithium battery. The only difference from Example 5 is that the formula of the lithium replenishing slurry is different. Specifically, the mass ratio of lithium replenishing particles (binary lithium compound Li2O), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 69%:5%:16%:10%. The remaining operations are consistent with those in Example 5 to prepare the corresponding lithium battery.

[0128] Embodiment 11

[0129] This comparative example involves the preparation of a lithium-replenishing slurry and a lithium battery. The only difference from Example 1 is that the formula of the lithium-replenishing slurry is different, specifically, the mass ratio of lithium-replenishing particles (lithium-rich compound Li2NiO2), microorganisms (yeast), conductive agent (graphene), and binder (polyvinyl alcohol) is 69%:5%:16%:10%, and other operations are consistent with Example 1 to prepare the corresponding lithium battery.

[0130] Comparative Example 1

[0131] This comparative example relates to the preparation of a lithium battery, which is different from Example 2 in that: the positive electrode slurry does not contain lithium supplement slurry, specifically: the positive electrode active material, the conductive agent SP, the conductive agent CNT and the binder PVDF are mixed in a mass ratio of 98.5%:0.5%:0.4%:0.6% to obtain a mixed material, and the mixed material is fully stirred in NMP to obtain the corresponding positive electrode slurry.

[0132] The other operations are consistent with those in Example 2, and the corresponding lithium battery is prepared.

[0133] Comparative Example 2

[0134] This comparative example involves the preparation of a lithium battery, which differs from Example 1 in that the formula of the lithium replenishing slurry is different, and an equal amount of lithium replenishing particles are used instead of microorganisms. Specifically, the mass ratio of lithium replenishing particles (lithium-rich compound Li2NiO2), conductive agent (graphene), and binder (polyvinyl alcohol) is 74:16:10.

[0135] Comparative Example 3

[0136] This comparative example involves the preparation of a lithium battery, which differs from Example 2 in that: the formula of the lithium replenishing slurry is different, and an equal amount of lithium replenishing particles are used instead of microorganisms. Specifically, the mass ratio of lithium replenishing particles (lithium complex Li2S / Co), conductive agent (graphene), and binder (polyvinyl alcohol) is 78:12:10, and the remaining operations are consistent with Example 2 to prepare the corresponding lithium battery.

[0137] Comparative Example 4

[0138] This comparative example involves the preparation of a lithium battery, which differs from Example 5 in that the formula of the lithium replenishing slurry is different, and an equal amount of lithium replenishing particles are used to replace microorganisms. Specifically, the mass ratio of lithium replenishing particles (binary lithium compound Li2O), conductive agent (graphene), and binder (polyvinyl alcohol) is 74:16:10.

[0139] Comparative Example 5

[0140] This comparative example involves the preparation of a lithium supplement slurry and a lithium battery, which is different from Example 1 in that the preparation of the lithium supplement slurry is different, an equal amount of glucose is used to replace yeast, and the remaining operations are consistent with those in Example 1 to prepare the corresponding lithium battery.

[0141] Comparative Example 6

[0142] This comparative example involves the preparation of a lithium supplement slurry and a lithium battery. The difference from Example 1 is that the temperature for preparing the lithium supplement slurry is different, and the stirring and heating treatment is performed at 40° C. The remaining operations are consistent with those in Example 1, and the corresponding lithium battery is prepared.

[0143] Comparative Example 7

[0144] This comparative example involves the preparation of a lithium supplement slurry and a lithium battery. The difference from Example 1 is that the temperature for preparing the lithium supplement slurry is different, and the stirring and heating treatment is performed at 100° C. The other operations are consistent with those in Example 1, and the corresponding lithium battery is prepared.

[0145] The relevant parameters of the lithium supplement slurry prepared in the above embodiments and comparative examples and the types of positive and negative active materials of lithium batteries are shown in Table 1 below:

[0146] Table 1

[0147]

[0148]

[0149] Performance Testing

[0150] The electrochemical performance tests of the lithium batteries prepared in the above examples and comparative examples are as follows:

[0151] First effect (first coulomb efficiency) test: the battery is allowed to stand at 25°C for 30 minutes, charged to 4.3V at a constant current rate of 0.5C, then charged at a constant voltage of 4.3V until the current is less than 0.05C, and the first charging capacity is recorded; the battery is allowed to stand for 30 minutes, discharged to 2.8V at a constant current rate of 1C, and the second charging capacity is recorded; after completion, the battery is allowed to stand for 15 minutes, and the constant current discharge is continued at 0.01C to 2.8V, and the third charging capacity is recorded. After completion, the battery is allowed to stand for 15 minutes; first effect = total discharge capacity / first charging capacity, total discharge capacity = first charging capacity + second charging capacity + third charging capacity.

[0152] Internal resistance test: Charge at a constant current of 0.5C for 1.5 hours, then let it stand for 5 minutes, and use an internal resistance tester to test the internal resistance.

[0153] K value test: after capacity division, the capacity is charged to 60% SOC, and the voltage OCV1 is recorded; after an interval of 24 hours, the voltage OCV2 is recorded; K value = (OCV1-OCV2) mV / 24 (H).

[0154] Discharge DCR test: 1) Charge to 4.3V at 0.33C, then charge at 4.3V constant voltage until the current is less than 0.05C, let stand for 30 minutes, repeat the above charge and discharge twice, and select the second discharge capacity as the standard capacity C0; 2) Let stand for 5 minutes, charge to 4.3V at 0.33C constant current, let stand for 30 minutes; 3) Then discharge at 0.33C constant current for 18 minutes (adjust to 90% SOC), let stand for 60 minutes, then discharge at 1C constant current for 30s (extract and record the discharge DCR of 10s), let stand for 5 minutes, charge at 0.33C constant current for 1.5 minutes (restore and adjust to 90% SOC); 4) Then use 0 .33C constant current discharge for 73.5min (adjusted to 50% SOC), stand for 60min, then discharge at a constant current rate of 1C for 30s (extract and record the discharge DCR of 10s), stand for 5min, charge at a constant current rate of 0.33C for 1.5min (restore and adjust to 50% SOC); 5) then discharge at a constant current rate of 0.33C for 55.5min (adjusted to 20% SOC), stand for 60min, then discharge at a constant current rate of 1C for 30s (extract and record the discharge DCR of 10s), stand for 5min, charge at a constant current rate of 0.33C for 1.5min (restore and adjust to 20% SOC), test cutoff (voltage selection corresponds to the range, ternary system 2.8-4.3V).

[0155] Rate discharge capacity retention rate: 1) Charge to 4.3V at a constant current of 0.33C, then charge at a constant voltage of 4.3V until the current is less than 0.05C, let stand for 30 minutes, repeat the above charge and discharge twice, and select the second discharge capacity as the standard capacity C0; 2) Then charge to 4.3V at a constant current of 0.33C, then charge at a constant voltage of 4.3V until the current is less than 0.05C, let stand for 30 minutes; then discharge to the voltage lower limit (X=0.33C, 1C, 3C) at a rate X, 3) Repeat 2) to obtain the discharge capacity of cells with different rates (the corresponding range of voltage selection, 2.8-4.3V for ternary system).

[0156] Cycle capacity retention test (50 cycles, 200 cycles, 400 cycles, 800 cycles): let stand for 5 minutes, charge at a constant current of 0.33C to 4.3V, then charge at a constant voltage of 4.3V until the battery is less than 0.05C, let stand for 30 minutes; then discharge at a constant current of 0.33C to 2.8V, after completion, let stand for 30 minutes; repeat the above charge and discharge operation to complete the charge and discharge cycle, and record the discharge capacity of each cycle in turn. For example, the capacity retention rate of the Nth cycle = the discharge capacity of the Nth cycle / the discharge capacity of the first cycle.

[0157] The test results are shown in 2 and 3 below:

[0158] Table 2

[0159]

[0160]

[0161] Table 3

[0162]

[0163]

[0164] As shown in Tables 2 and 3, Examples 1-11 not only effectively improve the first efficiency of the battery by adding a lithium replenishing slurry containing composite lithium replenishing particles to the positive electrode slurry for positive electrode lithium replenishment, but also effectively reduce the internal resistance of the battery and the self-discharge rate of the battery, and effectively improve the battery rate performance and cycle performance, compared with Comparative Examples 2-4 in which lithium replenishing particles are directly added for positive electrode lithium replenishment or Comparative Example 1 in which positive electrode lithium replenishment is not performed (Example 2 VS Comparative Example 1). It can be seen that by using microbial inactivation and pyrolysis to form an inert layer with a wrinkled structure on the surface of the lithium replenishing particles, it is beneficial to improve the first efficiency, rate performance and cycle performance of the battery after positive electrode lithium replenishment.

[0165] It can be seen from Examples 2, 8, 9 and Examples 5, 10 and Examples 1, 11 that the mass ratio of lithium-supplementing particles to microorganisms in the lithium-supplementing slurry will affect the first efficiency, rate and cycle performance of the battery. If the content of microorganisms in the lithium-supplementing slurry is too little, it is impossible to form an inert layer with obvious and complete wrinkle structure on the surface of the lithium-supplementing particles. The internal resistance of the battery prepared by the lithium-supplementing is high, and the rate performance and cycle performance are relatively poor. In addition, the proportion of lithium-supplementing agent particles in the lithium-supplementing slurry prepared in Example 9 is too small, which leads to insufficient lithium source on the one hand, and in the first SEI forming process, a good lithium-supplementing effect cannot be achieved, resulting in a low first efficiency; the residual carbon content after degradation of microorganisms with a relatively large proportion is relatively high. Although the conductivity is retained, the thick carbon layer also extends the path of ion transmission and increases the transmission resistance.

[0166] In Comparative Example 5, glucose is used to replace yeast as an additive to coat the lithium supplement particles. Compared with Example 1, the rate performance and cycle performance of the lithium battery prepared in Comparative Example 5 are significantly inferior to those in Example 1. This is because glucose cannot form a coating layer with a wrinkled structure on the surface of the lithium supplement particles, thereby failing to provide more lithium ion contact sites, resulting in a decrease in the first efficiency. In addition, it can be seen from Example 1 and Comparative Examples 6 and 7 that if the stirring temperature is too low or too high during the preparation of the lithium supplement slurry, the battery internal resistance, rate performance and cycle performance will be affected; if the oil bath temperature is too low, the microbial pyrolysis is insufficient, the carbon residue on the surface of the lithium supplement agent is insufficient (it cannot form a good conductivity), and the wrinkled carbon layer is less formed (it cannot provide more lithium ion contact points), resulting in a decrease in the first efficiency; if the oil bath temperature is too high, the microbial pyrolysis is too rapid, and losses occur before the lithium supplement particles are fully coated, resulting in insufficient carbon residue on the surface of the lithium supplement agent (it cannot form a good conductivity), increased internal resistance and reduced first efficiency.

[0167] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A composite lithium supplement particle, characterized in that: The composite lithium-supplementing particles include lithium-supplementing particles and an inert layer with a wrinkled structure coated on the surface of the lithium-supplementing particles, wherein the inert layer includes microbial pyrolysis products.

2. The composite lithium supplement particle according to claim 1, characterized in that: The lithium-supplementing particles include one or more of a binary lithium compound, a lithium-rich compound, and a lithium complex; the binary lithium compound is Li2O and / or LiF, the lithium-rich compound is Li2NiO2 and / or LiFeO4, and the lithium complex is a Li2S / Co complex; The microorganisms are fungi and / or bacteria; the fungi include yeasts, and the bacteria include actinomycetes.

3. The composite lithium supplement particle according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The particle size of the lithium supplement particles is 10-500 nm; (2) The thickness of the inert layer is 95-220 nm; (3) The particle size of the composite lithium supplement particles is 500nm-5μm; (4) The microbial pyrolysis product is a pyrolysis product of microorganisms at 60-80°C.

4. A method for preparing the composite lithium supplement particles according to any one of claims 1 to 3, characterized in that: include: Under an inert atmosphere, the lithium supplement particles and microorganisms are heated and stirred in the presence of a solvent to obtain the composite lithium supplement particles; the temperature of the heating and stirring treatment is 60-80° C., and the heating and stirring treatment time is not less than 30 minutes.

5. The preparation method according to claim 4, characterized in that: Contain at least one of the following characteristics: (1) The solvent is N-methylpyrrolidone; (2) The heating and stirring treatment time is 2-12 hours; (3) Firstly, the lithium supplement particles and the microorganisms are subjected to dry stirring treatment, and after being evenly mixed, a solvent is added for wet stirring treatment to obtain the composite lithium supplement particles; the temperature of the dry stirring treatment and the wet stirring treatment are both 60-80° C., and the time of the wet stirring treatment is not less than 0.5 h.

6. A lithium supplement slurry, characterized in that: The invention comprises the composite lithium supplement particles according to any one of claims 1 to 3 or the composite lithium supplement particles prepared by the preparation method according to claim 4 or 5.

7. The lithium supplement slurry according to claim 6, characterized in that: The formula of the lithium supplement slurry comprises the following components by mass: 50-60 parts of lithium supplement particles, 10-25 parts of microorganisms, 10-25 parts of conductive agents, and 5-20 parts of binders; Preferably, when the lithium-supplementing particles are binary lithium compounds, the formula of the lithium-supplementing slurry comprises the following components by mass: 50-60 parts of lithium-supplementing particles, 10-20 parts of microorganisms, 15-25 parts of conductive agents, and 5-15 parts of binders; Preferably, when the lithium-supplementing particles are lithium-rich compounds, the formula of the lithium-supplementing slurry comprises the following components by mass: 50-60 parts of lithium-supplementing particles, 10-20 parts of microorganisms, 10-20 parts of conductive agents, and 10-20 parts of binders; Preferably, when the lithium-supplementing particles are lithium composites, the formula of the lithium-supplementing slurry comprises the following components by mass: 50-60 parts of lithium-supplementing particles, 20-25 parts of microorganisms, 10-20 parts of conductive agents, and 5-15 parts of binders; Preferably, the conductive agent is selected from one or more of conductive carbon black, conductive graphite, conductive fiber, carbon nanotube, and graphene; Preferably, the binder is selected from one or more of PVDF, SBR, CMC, PAA, PAN, SA, PVA, PMMA, HNBR, and PTFE.

8. A method for preparing the lithium supplement slurry according to claim 6 or 7, characterized in that: The following steps are involved: (1) Under an inert atmosphere, stirring the lithium supplement particles and the microorganisms in the presence of a solvent at 60-80° C. for not less than 30 minutes to obtain a mixture; (2) Adding a conductive agent and a binder to the mixture prepared in step (1) and stirring the mixture to obtain a lithium supplement slurry containing composite lithium supplement particles.

9. A positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer is obtained by coating a positive electrode slurry on the current collector and drying the positive electrode slurry, characterized in that: The positive electrode slurry comprises the composite lithium supplement particles according to any one of claims 1 to 3 or the lithium supplement slurry according to claim 6 or 7; and / or, The positive electrode plate also includes a lithium replenishing layer, which is arranged on a side of the positive electrode active layer away from the current collector or on a side of the current collector where the positive electrode active layer is not arranged; the lithium replenishing layer is obtained by coating the lithium replenishing slurry described in claim 6 or 7 on the current collector or the positive electrode active layer and drying it.

10. A lithium battery, characterized in that: Contains the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Lithium supplement additive with composite structure, preparation method of lithium supplement additive, electrode plate and battery

    CN121528909A